Menggali Potensi Objek Wisata Riam Sengiang Desa Kempangai Kecamatan Ella Hilir Kabupaten Melawi - Yohanes, Yulius; Iku, Agustina Bete; Pradita, Antonia Eka; Jessika, Angelina; Viany, Irena (Journal of Community Service and Society Empowerment, 2024)
This research aims to explore the potential of the Riam Sengiang tourist attraction in Kempangai Village, Ella Hilir District, Melawi Regency. Melawi Regency is also known as an area rich in natural beauty and has a variety of amazing tourism potential. The tourism sector is a sector that can be managed by local governments to improve the regional economy and local communities. This research uses a qualitative method with a descriptive approach. Data was collected through reviews of journals, books, news, statutory regulations and other documents. SWOT analysis is used to identify strengths, weaknesses, opportunities and threats related to Riam Sengiang's potential as a tourist attraction. The research results show that Riam Sengiang has strengths, especially in its natural beauty, tourism product development opportunities, and partnership opportunities with other parties. However, there are also weaknesses that hinder the development of Riam Sengiang's potential as a tourist attraction, namely limited road access and facilities. Apart from that, there is also a threat faced, namely sustainable environmental destruction. Therefore, it is necessary to improve infrastructure, develop facilities and maintain the environment to optimize the tourism potential of Riam Sengiang. This research provides an understanding of the important role of government in managing tourist attractions to improve the welfare of local communities.